The global financial crisis: Lessons for European Integration - Marek Dabrowski (Center for Social and Economic Research (CASE), 2009)
The purpose of this paper is to analyze the various challenges facing European integration and the EU institutional architecture as result of the global financial crisis. The European integration process is not yet complete, both in terms of its content and geographical coverage. It can be viewed as a kind of intermediate hybrid between an international organization and a federation, subject to further evolution. This is also true of the Single European Market and the Economic and Monetary Union, which form the core of the EU economic architecture. Certain policy prerogatives (such as external trade, competition, and the Common Agriculture Policy) are delegated to the supranational level while others (such as financial supervision or fiscal policy) remain largely in the hands of national authorities. The EU's limited fiscal capacity has proven to be the most critical constraint in being able to respond to the crisis in a proper and well coordinated manner at the Union level. The EU budget is limited to 1% of its GDP and finances only specific policies. The EU cannot borrow or provide credit guarantees. There are several obstacles to coordinating national fiscal policies, which are both of an economic and institutional-political character. So the possibility of implementing a joint fiscal intervention, even for such emergency tasks as rescuing the pan-European financial institutions or member countries in distress, is very limited. These limitations have often led to the nationalization of the fiscal response, including offering emergency rescue packages to troubled financial institutions or non-financial corporations which. This, in turn, has often led to economic nationalism,” which undermines the basic principles of the Single European Market. The distressed financial markets also test the macroeconomic coherence of the EU and EMU, placing pressure on those countries which are considered financially fragile or potentially insolvent. They face surging risk premia, capital outflow, depreciating currencies, and sovereign borrowing constraints. Again, the EU does not have enough fiscal resources to provide rescue packages, and an increasing number of member-states must apply for IMF assistance. The best solution would be to increase, at least temporarily, the EU fiscal potential. This would allow providing rescue packages to both troubled financial institutions and member states in a coordinated way. In addition, the EU must act to complete the lacking elements of the Single European market architecture (such as European financial supervision) and help in strengthening global policy and regulatory coordination.
Keywords: F33; F42; G15; G18; H87; 330; financial crisis; European integration; European Union; Economic and Monetary Union; fiscal policy; financial supervision; global financial architecture; IMF; Finanzkrise; Internationaler Finanzmarkt; Europäische Integration; Eurozone; EU-Binnenmarkt; Finanzpolitik; EU-Politik; EU-Staaten